2013
DOI: 10.1155/2013/593761
|View full text |Cite
|
Sign up to set email alerts
|

Grape Polyphenols Increase the Activity of HDL Enzymes in Old and Obese Rats

Abstract: HDL particles are protein-rich particles that act as a vehicle for reverse cholesterol transport from tissues to the liver. The purpose of this study was to investigate age-dependent changes in the functional activity of HDL and the effect of high-energy diet on this index, as well as to correct it under the influence of grape polyphenols from “Enoant” obtained from Vitis vinifera grapes. We observed the age-dependent composition changes in HDL particle. It was shown that total lipids and triacylglycerol (TG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
(43 reference statements)
2
25
0
1
Order By: Relevance
“…This effect was reasoned to the increase in HDL paraoxonase HDL PON that leads to increasing the cellular response via the increase in the receptors (20). HDL increasing is linked to the generation of is oflavone genistein by polyphenols that leads to activation of protein kinase mitogen (21). In the case of glucose, our study shows a significant decrease in G3 when compared to G2 and G1 at 21 and 42 day of age.…”
Section: Discussionmentioning
confidence: 52%
“…This effect was reasoned to the increase in HDL paraoxonase HDL PON that leads to increasing the cellular response via the increase in the receptors (20). HDL increasing is linked to the generation of is oflavone genistein by polyphenols that leads to activation of protein kinase mitogen (21). In the case of glucose, our study shows a significant decrease in G3 when compared to G2 and G1 at 21 and 42 day of age.…”
Section: Discussionmentioning
confidence: 52%
“…Our research group found a positive association with a strong increase of HDL after G8000 intake. Zagayko et al (2013) observed a reduction of cholesterol ester transfer protein (CETP) and an increase of HDL enzymes activity in rats after 21 days of grape polyphenol concentrate. These findings are in good agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that should be considered is the age of participants cited in the studies. Although there is no evidence in the literature demonstrating the effects of age in response to grape juice consumption on memory and other clinical-functional outcomes, it has been reported in experimental findings that the consumption of polyphenols acts in an agedependent manner in some biomarkers, which could affect some clinical data [44]. Then, these results led us to infer that the age and time of grape juice consumption might be strictly related to its impact on memory performance.…”
Section: Sift Deskmentioning
confidence: 91%